Explicit collusion under antitrust enforcement - Igor Mouraviev (Bielefeld University, Center for Mathematical Economics (IMW), 2013)
The article seeks to fill the gap between tacit and explicit collusion in a setting where firms observe only their own output levels and a common price, which includes a stochastic component. Without communication, firms fail to discriminate between random shocks and marginal deviations, which constrains the scope for collusion. By eliminating uncertainty about what has happened, communication facilitates detection of deviations but reduces collusive profits due to the risk of exposure to legal sanctions. With the optimal collusive strategy, firms communicate only if the market price falls somewhat below the trigger price. Moreover, they tend to communicate more often as they become less patient, a cartel grows in size, or demand uncertainty rises.
urn:nbn:de:0070-pub-26753051
Keywords: D82; L41; 330; Collusion; Communication; Imperfect Monitoring; Frequency of Meetings